1994
DOI: 10.1111/j.1432-1033.1994.1151b.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Activity Characterization of Glucagon‐Like Peptide‐1

Abstract: Glucagon-like peptide-1 is a gastrointestinal hormone that strongly stimulates insulin release via specific receptors on the pancreatic p-cell. To characterize the side-chain groups required for interaction of glucagon-like peptide-1 with its receptor, we performed binding studies with alanine-substituted glucagon-like peptide-1 analogues on RINmSF insulinoma cells. The binding affinity and biological activity of glucagon-like peptide-1 have been found to be sensitive to alanine exchanges in the N-terminal pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 26 publications
6
89
0
Order By: Relevance
“…However, the mechanisms underlying binding and activation of this receptor and other members of this family are poorly understood and the development of small molecule ligands is problematic. This has been approached by previous structure-activity, mutagenesis and chimeric studies (18,(27)(28)(29)(30)(31)(32)(33)(34)(35). In this study, we used photoaffinity labeling to demonstrate that the carboxyl terminus of GLP1 is in approximation with the amino terminus of the receptor when docked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms underlying binding and activation of this receptor and other members of this family are poorly understood and the development of small molecule ligands is problematic. This has been approached by previous structure-activity, mutagenesis and chimeric studies (18,(27)(28)(29)(30)(31)(32)(33)(34)(35). In this study, we used photoaffinity labeling to demonstrate that the carboxyl terminus of GLP1 is in approximation with the amino terminus of the receptor when docked.…”
Section: Discussionmentioning
confidence: 99%
“…Alanine-scanning of GLP1 has implicated positions 7, 10, 12, 13, 15, 26, 28, and 29 as being critical for receptor binding (18,30), whereas substitutions at positions 24 and 35 have minimal effects on GLP1 receptor binding and activation (18). This is consistent with our incorporation of a Bpa in these positions.…”
mentioning
confidence: 99%
“…, Gly 4 , Thr 7 , and Asp 9 are important for receptor binding and activation (30,31 7 . Thus, similarities in the ligand binding pocket structures of GLP1R, GCGR, GCRPR, and GLP2R may accommodate the conserved residues in the N-terminal moieties of the peptides.…”
mentioning
confidence: 99%
“…Alanine scanning analysis revealed that His 1 , Gly 4 , Thr 7 , and Asp 9 in the N-terminal portion of GLP-1 are important for receptor binding and activation (30,31). Recently, by using chimeric GLP1R/GIPR together with chimeric GLP-1/GIP peptides, we identified interactions of His 1 and Thr 7 of GLP-1 with Ile 196 /Lys 197 at TMH2, Met 233 at ECL1, and Asn 302 at ECL2 of GLP1R (32).…”
mentioning
confidence: 99%
“…Asp at position 3 is conserved across all the mature SCT peptides and this residue has a role in adenyl cyclase (AC) stimulation and interacts with the basic residues in the second transmembrane (TM) helix of the secretin GPCRs (Cardoso et al 2010). Other conserved residues such as His1 and Phe6 are key amino acids in secretin's GPCR-binding affinity (Gourlet et al 1991 Gallwitz et al 1994, Irwin 2001, Bourgault et al 2009). …”
Section: Structural Evolution Of Secretinmentioning
confidence: 99%